Molecular Characteristics, Oncogenic Roles, and Relevant Immune and Pharmacogenomic Features of EVA1B in Colorectal Cancer - Ma, Bin; Wang, Kangchun; Liang, Yu; Meng, Qingkai; Li, Yongmin (Frontiers in Immunology, 2022)
Objective: EVA1B, a protein coding gene, which is a critical paralog of EVA1A gene. Herein, our study was conducted for investigation of the roles of EVA1B in colorectal cancer (CRC) progression and prognosis. Methods: Pan-cancer analyses were conducted for analyzing expression, genetic and epigenetic alterations, and immunological characteristics of EVA1B. Especially, immunological characteristics and mutational landscape were compared between high and low EVA1B expression groups in combined TCGA-COAD and TCGA-READ datasets. Through Random Survival Forest analyses, an EVA1B-derived genomic model was developed and its prognostic value was verified in external datasets (GSE14333, GSE39582 and GSE87211). Drug sensitivity was compared between high and low risk subpopulations. A nomogram was conducted through integration of independent factors. Results: EVA1B presented remarkable up-regulation in most cancer types, especially CRC. EVA1B expression was significantly linked to DNA methyltransferases, DNA mismatch repair genes, m6A regulators, TMB and MSI across pan-cancer. High EVA1B expression indicated undesirable CRC patients’ prognosis. Additionally, its up-regulation was linked to enhanced immune cell infiltration, increased stromal and immune activation, and elevated activities of cancer immunity cycle. Higher frequencies of amplification and deletion were investigated in high EVA1B expression subpopulation. Following verification, EVA1B-derived genomic model reliably predicted patients’ prognosis and drug responses. The nomogram (age, stage, EVA1B-derived risk score) was conducted for quantifying an individual’s survival probabilities. Conclusion: Collectively, our findings provided valuable resource for guiding the mechanisms and therapeutic analyses of EVA1B in CRC.